1986
DOI: 10.1029/ja091ia05p05567
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of solar EUV, UV, and 10,830‐Å radiations

Abstract: The temporal characteristics of the full-disk chromospheric EUV fluxes agree well with those of the ground-based'measurements of the chromospheric He I absorption line at 10,830 A and differ systematically from those of the coronal EUV and 10.7-cm flux. The ratio of the flux increase during the rise of solar cycle 21 to that during solar rotation variations is uniformly high for the chromospheric EUV and corroborating 10,830-/!/fluxes, highest for the transition region and'"cool" coronal EUV fluxes (T < 2 x 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 14 publications
4
50
1
Order By: Relevance
“…Our results is consistent with the findings reported by (Donnelly, 1969), (Donnelly, 1971), (Donnelly, 1976), (Donnelly et al, 1986a), where a study of extreme UV (EUV) flashes of solar flares observed via SFD was made. In the cited references it was shown that the relative strength of impulsive EUV emission from flares decreases with increasing CMD and average peak frequency deviation is also significantly lower for SFD's associated with Hα flares at large CMD.…”
Section: Discussionsupporting
confidence: 83%
“…Our results is consistent with the findings reported by (Donnelly, 1969), (Donnelly, 1971), (Donnelly, 1976), (Donnelly et al, 1986a), where a study of extreme UV (EUV) flashes of solar flares observed via SFD was made. In the cited references it was shown that the relative strength of impulsive EUV emission from flares decreases with increasing CMD and average peak frequency deviation is also significantly lower for SFD's associated with Hα flares at large CMD.…”
Section: Discussionsupporting
confidence: 83%
“…Donnelly et al (1986) showed that the ratio of the amplitudes of the long-term variations to short-term variations was highest (about 2 to 3) for EUV (170-660Å), about 2 for chromospheric UV, EUV and 10 830Å He I, and less than 1.5 for F10, Rz and Ca-K Plage index. Several details about the 13-day and 27-day variations were presented by them.…”
Section: Introductionmentioning
confidence: 99%
“…The next major attempt to make a comparative study of the variations of different solar indices was by Donnelly et al (1986), using the AE-E data of 15 wavelength groups (170-1220Å, Hinteregger et al, 1981), the He I line 10 830Å, the F10 flux, and sunspots. Donnelly et al (1986) showed that the ratio of the amplitudes of the long-term variations to short-term variations was highest (about 2 to 3) for EUV (170-660Å), about 2 for chromospheric UV, EUV and 10 830Å He I, and less than 1.5 for F10, Rz and Ca-K Plage index.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors using the sunspot number Rz or the 10.7-cm solar radio flux, F•o.7, as an indicator of solar activity variability, concluded that stratospheric temperature variations did not show a consistent relationship with the solar cycle variations [Mohanakumar, 1987]. Indeed, the solar spectral range mainly involved in stratospheric heating (200-300 nm), UV, has also temporal variations that differs from those of Rz or F•o.7 [Donnelly et al, 1986]. Labitzke and Van Loon [1994] [Van Loon and Labitzke, 1993] have analyzed the northern hemisphere stratospheric circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The EUV flux is parameterized as a linear function of either Rz or F• o.v [Cook et al, 1980;Tobiska and Barth, 1990;Donnelly et al, 1986]. So that, the peak electron density of the ionospheric F 2 layer (at around 400 km height), N .... which is proportional to EUV flux [Hoegy and Mahajan, 1992 Table 1.…”
Section: Introductionmentioning
confidence: 99%